1980
DOI: 10.1128/aem.40.6.994-1002.1980
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of pathogenic bacteria in the oyster, Crassostrea commercialis, during depuration, re-laying, and storage

Abstract: Oysters (Crassostrea commercialis) harvested from major cultivation areas within the state of New South Wales, Australia, were commonly contaminated with low levels of the food-poisoning organisms Bacillus cereus, Clostridium perfringens, and Vibrio parahaemolyticus. Salmonella was found in oysters on only one occasion. These bacteria were cleansed from oysters during oyster purification by relaying in a non-polluted waterway. Oysters were laboratory contaminated to levels in excess of 1,000 cells per g with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…In general, oysters were found to reduce S. typhimurium to a low level within < 5 d after relaying, and to a non-detectable level ( < 1 per 200 g) within 5 to 9 d under a wide variety of environmental conditions. Similar results have been obtained by other researchers (21,28). S. montevideo responded with an initial reduc- tion to levels of ^1 cell per gram in 3 to 8 d after relaying, but persisted in oysters at a detectable level (>1 to <200 cells/200 g) for as long as 28 d. Failure of the oysters to eliminate this species is not understood, but may signal that low levels of other species of salmonellae could persist for lengthy periods in oysters, or that failure to detect other salmonellae species is related to the techniques of recovery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In general, oysters were found to reduce S. typhimurium to a low level within < 5 d after relaying, and to a non-detectable level ( < 1 per 200 g) within 5 to 9 d under a wide variety of environmental conditions. Similar results have been obtained by other researchers (21,28). S. montevideo responded with an initial reduc- tion to levels of ^1 cell per gram in 3 to 8 d after relaying, but persisted in oysters at a detectable level (>1 to <200 cells/200 g) for as long as 28 d. Failure of the oysters to eliminate this species is not understood, but may signal that low levels of other species of salmonellae could persist for lengthy periods in oysters, or that failure to detect other salmonellae species is related to the techniques of recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Relaying waters may contain some indicator bacteria and this study suggested that fecal coliforms may not be useful as end-point indicators for this method of oyster purification. Depuration (7,9) and relaying (3,25,28) are methods…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the shells were washed with 70% ethanol and were depurated for 72 h in filtered, UVsterilised seawater with constant aeration according to the scheduled depuration process (FDA, 1992). The transient microbiota was removed from the oysters using methods previously reported by Son and Fleet (1980) and Lee et al (2008). The external valves were thoroughly cleaned to remove surface contamination, and the oysters were then carefully opened, leaving the animal intact.…”
Section: Oyster Collectionmentioning
confidence: 99%